ANALISIS HUKUM EKONOMI SYARIAH TERHADAP PENYELESAIAN PEMBAYARAN BERMASALAH DI PERBANKAN SYARIAH - Almirah Luthfiyah Nur Aurellia; Fauzatul Laily Nisa (CV. ALIM'SPUBLISHING, 2024)
Problematic financing is an unavoidable risk for banks in providing financial services. This situation can occur when the debtor fails to fulfill his obligations to the bank, either due to business failure or deliberately not paying financing obligations according to the agreement due to the debtor's bad character. This research aims to identify the factors and impacts of problematic financing in sharia banking, the resolution mechanism, as well as the regulation and relevance of sharia economic law in resolving these problems. The method used is normative juridical (legal research) which focuses on studying the application of applicable positive legal rules or norms and is related to the substance of the research. The research results show that problematic financing factors originate from internal factors (managerial errors) and external factors (debtor errors). Resolving problematic financing can be done through alternative dispute resolution or litigation (resolved by the court). Meanwhile, sharia economic law regulations regarding the resolution of problematic financing can be carried out by means of tahkim, through qadhi, or resolved by means of al-ishlah.